DOI: 10.11606/t.11.2020.tde-20200111-145141
|View full text |Cite
|
Sign up to set email alerts
|

O déficit de irrigação como estratégia de manejo da agua em feijoeiro (>i<Phaseolus vulgaris>/i< L.)

Abstract: a. m, n : parâmetros empíricos de ajuste da curva de retenção de água no solo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Taking 60% AW as an example, expected irrigation depths vary, for percentiles 10 and 90, from 120 to 230 mm, in 6 to 11 applications of about 20 mm, for the fall growing season, and from 230 to 330 mm, in 11 to 15 applications, for the crop grown during the spring. Those results agree with depth and number of application observed in field experiments conducted in the study area, as reported by Faria et al (1997a), and are in accordance to the results obtained for other regions in Brazil, as reported by Saad (1996), Queiroz et al (1996), and Calheiros et al (1996).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Taking 60% AW as an example, expected irrigation depths vary, for percentiles 10 and 90, from 120 to 230 mm, in 6 to 11 applications of about 20 mm, for the fall growing season, and from 230 to 330 mm, in 11 to 15 applications, for the crop grown during the spring. Those results agree with depth and number of application observed in field experiments conducted in the study area, as reported by Faria et al (1997a), and are in accordance to the results obtained for other regions in Brazil, as reported by Saad (1996), Queiroz et al (1996), and Calheiros et al (1996).…”
Section: Resultssupporting
confidence: 93%
“…Several experiments concerning critical irrigation thresholds were reported in the literature (Gallegos and Shibata, 1989;Sangakkara, 1994, Faria et al, 1997a. Optimum irrigation strategies for dry beans were determined in São Paulo, in two studies using land (Queiroz et al, 1996) and water (Calheiros et al, 1996;Saad, 1996) as limiting factors. They used a crop-water production function derived from experiments to calculate net benefits of application of different irrigation depths, by means of a well established analytical method of economic analysis (English, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Cabe destacar ainda que, para as plantas atingirem a sua máxima produtividade, elas necessitam receber água em quantidade adequada e nos momentos oportunos (SAAD, 2009).…”
Section: Introductionunclassified